The Effect of Economic Growth Rate Uncertainty on Financing Small and Medium Enterprises in Iran - Davoud Safi Dastjerdi; Seyed Komeil Tayebi; Nasser Elahi (International Journal of Business and Development Studies, 2020)
Today, small and medium-sized enterprises (SMEs) play a key role in both developing and developed economies. However, the uncertainty of macroeconomic indicators, such as economic growth, may affect financing and investment of the SMEs in an economy. The present study explores the effect of the economic growth rate uncertainty on financing SMEs in Iran. To this end, the study has applied the Brownian motion approach to calculate the uncertainty of the economic growth rate. The study has also considered relevant data of the Iranian SMEs compiled by the Comprehensive Database of All Listed Companies (CODAL). We have examined the SMEs with less than 100 employees throughout 2011-2017. The empirical results show that the effect of the economic growth rate uncertainty on the selected Iranian SMEs financing has been negative and statistically significant, while it seems an effective challenge to such firms in order to finance their productive investment.JEL Classification:D81, G21, L25, E43.